2016
DOI: 10.18632/oncotarget.9076
|View full text |Cite
|
Sign up to set email alerts
|

Abundant PD-L1 expression in Epstein-Barr Virus-infected gastric cancers

Abstract: Gastric cancer (GC) is a deadly disease with limited treatment options. Recent studies with PD-1 inhibition have shown promising results in GC, but key questions remain regarding which GC subclass may respond best. In other cancers, expression of the PD-1 ligand PD-L1 has been shown to identify cancers with greater likelihood of response to PD-1 blockade. We here show with immunohistochemistry that Epstein-Barr Virus (EBV)+ GCs (n = 32) have robust PD-L1 expression not seen in other GCs. In EBV+ GC, we observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
243
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(271 citation statements)
references
References 25 publications
18
243
1
9
Order By: Relevance
“…Several studies have demonstrated that PD-L1 immunoexpression is heterogeneous in GC, as in other tumour models. PD-L1 overexpression is associated with high densities of CD3+ and CD8+ tumour-infiltrating lymphocytes [67][68][69], GC with lymphoid stroma morphology [70], and both an EBV+ and MSI-high molecular status [69,[71][72][73][74]. However, the correlation with PD-L1 amplification, prognosis, and response to targeted immunotherapies is still debated and deserves further study.…”
Section: Moving Towards Molecular Subtyping and Precision Medicinementioning
confidence: 99%
“…Several studies have demonstrated that PD-L1 immunoexpression is heterogeneous in GC, as in other tumour models. PD-L1 overexpression is associated with high densities of CD3+ and CD8+ tumour-infiltrating lymphocytes [67][68][69], GC with lymphoid stroma morphology [70], and both an EBV+ and MSI-high molecular status [69,[71][72][73][74]. However, the correlation with PD-L1 amplification, prognosis, and response to targeted immunotherapies is still debated and deserves further study.…”
Section: Moving Towards Molecular Subtyping and Precision Medicinementioning
confidence: 99%
“…The expression of PD-L1 significantly increases in both tumor and stromal cells in the EBV and MSI subtype [45]. Herein, a high expression of PD-L1 might predict a better response to neoadjuvant chemotherapy in EAC, and it is associated with a higher pathological response [46].…”
Section: Immunotherapy In Eacmentioning
confidence: 93%
“…These subtypes demonstrate diversity in immunological targets, with EBV and MSI subtypes the most promising in this regard. Amplification of 9p encoding PD-L1 and PD-L2 genes is often found in EBV-positive tumours, and high levels of PD-L1 protein expression has been demonstrated on tumour cells in EBV-positive gastric adenocarcinoma [43]. Germline or acquired defects in mismatch repair processes lead to high levels of mutations and neo-antigen presentation in MSI gastric cancer, which in turn leads to tumour-infiltrating lymphocyte invasion and PD-L1 expression [44,45].…”
Section: Gastric-cancer Subtypes and Immune Responsementioning
confidence: 99%
“…Germline or acquired defects in mismatch repair processes lead to high levels of mutations and neo-antigen presentation in MSI gastric cancer, which in turn leads to tumour-infiltrating lymphocyte invasion and PD-L1 expression [44,45]. Both EBV and MSI gastric adenocarcinoma have high levels expression of gene signatures which are associated with response to PD-1 therapy [22,43]. However, although EBV and MSI gastric cancer may be more likely to benefit from immunotherapy, because of their innate positive prognostic value, these subtypes are less often found in patients with advanced disease than other subtypes.…”
Section: Gastric-cancer Subtypes and Immune Responsementioning
confidence: 99%